Features of the development of physical qualities of water polo players - Briskin, Y.; Ostrovskyy, M.; Chaplinskyy, M.; Sydorko, O.; Polehoiko, M.; Ostrovsky, N.; Pityn, M. (Journal of Physical Education and Sport, 2015)
Application of power training exercises that are similar in structure and composition to competitive acts of water polo players and their purposeful use for developing power endurance, ultimate speed and explosive power ensure their greatest development. It has been recognized that the most effective is the use of speed training exercises in the middle of the training session. In water polo training the practice of developing speed skills at the end of training session is the least effective. Combination of speed qualities training variants at different parts of training session throughout the year-round cycle of training adds to the positive effect of speed qualification of water polo players in general. The experimental program of strength training of qualified water polo players, which provided purposeful development of strength capabilities (maximum, speed, explosive strength and strength endurance) by applying specific exercises, which correspond to features of competitive activity of water polo players, indicated its effectiveness in the main experiment. In a result of experimental program implementation of strength training of experimental group athletes in comparison with the control group, significant improvements (p <0.05) according to strength rated were occurred. The experimental program of strength training of qualified water polo players, which provided testing of expediency of structuring use of speed exercises within the training sessions (at the beginning, at mid and in the end of the main part of training) also has shown effectiveness in both previous and in main experiments. The most effective for the development of speed qualities of skilled water polo players is the use of high-speed swimming exercises in the second third of the main part of training session.